A molecular mechanism for eflornithine resistance in African trypanosomes. - Isabel M Vincent; Darren Creek; David G Watson; Mohammed A Kamleh; Debra J Woods; Pui Ee Wong; Richard J S Burchmore; Michael P Barrett (PLoS Pathogens)
Human African trypanosomiasis, endemic to sub-Saharan Africa, is invariably fatal if untreated. Its causative agent is the protozoan parasite Trypanosoma brucei. Eflornithine is used as a first line treatment for human African trypanosomiasis, but there is a risk that resistance could thwart its use, even when used in combination therapy with nifurtimox. Eflornithine resistant trypanosomes were selected in vitro and subjected to biochemical and genetic analysis. The resistance phenotype was verified in vivo. Here we report the molecular basis of resistance. While the drug's target, ornithine decarboxylase, was unaltered in resistant cells and changes to levels of metabolites in the targeted polyamine pathway were not apparent, the accumulation of eflornithine was shown to be diminished in resistant lines. An amino acid transporter gene, TbAAT6 (Tb927.8.5450), was found to be deleted in two lines independently selected for resistance. Ablating expression of this gene in wildtype cells using RNA interference led to acquisition of resistance while expression of an ectopic copy of the gene introduced into the resistant deletion lines restored sensitivity, confirming the role of TbAAT6 in eflornithine action. Eflornithine resistance is easy to select through loss of a putative amino acid transporter, TbAAT6. The loss of this transporter will be easily identified in the field using a simple PCR test, enabling more appropriate chemotherapy to be administered.